The role of education attainment on 24-hour movement behavior in emerging adults: evidence from a population-based study - You, Yanwei; Mo, Leiyu; Tong, Jing; Chen, Xiangyu; You, Yujun (Frontiers in Public Health, 2024)
Purpose The purpose of this study was to explore the relationship between education level and health behavior including sleep, work activity, exercise activity, and sedentary behavior among emerging adults. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2018. The study sample included 4,484 emerging adults aged 18–25 years and the weighted participants were 30,057,813. Weighted multivariable regression analysis was performed to investigate the association between education level and the aforementioned health behavior, adjusting for age, gender, race/ethnicity, marital status, poverty-income ratio, BMI, smoking, and alcohol drinking status. Results This study revealed that higher education level was associated with shorter sleep duration [Fully adjusted model, β (95% CI): −0.588 (−0.929, −0.246), p < 0.001]. Additionally, those with higher education levels were more likely to allocate time in sedentary behavior [β (95% CI): 90.162 (41.087, 139.238), p < 0.001]. Moreover, higher education level was related to less work activity [β (95% CI): −806.991 (−1,500.280, −113.703), p = 0.023] and more exercise activity time [β (95% CI): 118.196 (−21.992, 258.385), p = 0.097]. Subgroup analysis further verified this trend and detected that males with higher education level tended to participate in less work activity [β (95% CI): −1,139.972 (−2,136.707, −143.237), p = 0.026] while females with higher education level tended to engage in more exercise activity [Fully adjusted model, β (95% CI): 141.709 (45.468, 237.950), p = 0.004]. Conclusion This study highlighted the importance of education level as a significant factor in promoting healthy behavior among emerging adults. The findings underscored the need for the Ministry of Education to prioritize educating this demographic about the significance of maintaining adequate sleep patterns and reducing sedentary habits. Encouraging them to allocate more time for work and physical activities can significantly contribute to their overall wellbeing and success, ultimately fostering a healthier next generation.